Extraction of natural antioxidants from strawberry guava leaf by conventional and non-conventional techniques. Issue 8 (3rd August 2021) - Coelho, Jaina Mara Pigosso; Johann, Gracielle; da Silva, Edson Antonio; Palú, Fernando; Vieira, Melissa Gurgel Adeodato
Abstract: Natural extracts of strawberry guava leaf were obtained using the following techniques: supercritical CO2 extraction (at 14, 17, and 20 MPa and 35, 45, and 55 °C); dynamic maceration with hexane solvent; Soxhlet extraction; ultrasound-assisted extraction (at 40, 50, and 60 °C; 100, 300, and 500 W; 1:10, 15, and 20 g mL −1 ), and supercritical extraction followed by ultrasound. Yield results were 3.59% for Soxhlet extraction, 2.68% for ultrasound-assisted extraction, 1.46% for ultrasound re-extraction after supercritical extraction, 0.98% for dynamic maceration, and 0.86% for supercritical CO2 extraction. Natural extracts of strawberry guava leaves obtained via supercritical extraction were found to be rich in eudesmol, squalene, and vitamin E, in 11.03, 19.44, and 53.42% percentages, respectively. They also exhibited high antioxidant activity, 26.15 μg mL −1 . This result was directly related to the α-tocopherol present in vitamin E.